Hubungan Umur, Intensitas Merokok, Status Gizi, Lili Paris (Chlorophytum Comosum) Terhadap Kadar CO Asap Rokok Dan COHb Dalam Darah - ummu sholochah; Rizky Rahadian; Marsha Savira Agatha Putri (Dian Nuswantoro Semarang, 2021)
Polluted air especially indoors can cause serious problems compared to outdoors. One of the most common pollutants found indoors is carbon monoxide (CO). CO that binds to blood will form carboxyhemoglobin (COHb) bonds, the main source of CO in a closed room comes from cigarette smoke. CO levels that will enter the body are greater in smokers than non-smokers, paris lilies can reduce CO levels. The purpose of this study was to determine the relationship between age, smoking intensity, nutritional status, CO in indoor cigarette smoke and COHb. This research method is quantitative, room CO is measured at 3 sampling points 2 times and blood collection is carried out 2 times as much as 0.05 ml. Respondents in this study were 7 men aged 33-50 years. Yield of CO 4 ppm. COHb has a decreasing value of 0.717%. The value of simple linear regression analysis of the relationship between smoking intensity and COHb with the addition of 5 paris lilies R2 = 0.6379 means that it has a moderate relationship.Keywords: COHb, age, smoking intensity, nutritional status, indoor cigarette smoke CO